THE URGENCY OF REVOKING THE PROVISIONS OF THE CONSIGNMENT INSTITUTION AND THE CONSTRUCTION OF ITS REPLACEMENT IDEAL IN LAND ACQUISITION FOR DEVELOPMENT IN THE PUBLIC INTEREST - Intan Nevia Cahyana (Fakultas Hukum Universitas Trisakti, 2018)
Consignment is normatively against the principle of land acquisition which states that it’s not allowed to obtain land by any form of coercion by anyone to the right holder to hand the land and or receive compensation they don’t approve. The problem was how to the ideal construction of regulation of consignment which provides justice for public welfare. The research method used is a type of qualitative, the research paradigm is constructivism, the approach used was socio legal study which is a study which reviews law as a social symptom which can be observed in experience as behavioral pattern in the forms of social institutions. The research results were; Consignment is a form of abuse and act against law (onrechtsmatigheids overdaad) done by the government and land procurement committee officials. If this continues in land procurement, it will cause problems which end in conflicts and lengthy disputes, to reconstruct consignment institutions, it’s urgent to (1) revoke article on consignment as the basis of its implementation through legislative review, (2) revitalize land dispute resolution institution through mediation, (3) publish blue print to monitor the government for the success of developments performed fairly.Keywords: Consignment and State Control Right